Shareholders in the Dutch Eighteenth-Century Atlantic Trade - van der Blij, Koen (TSEG - The Low Countries Journal of Social and Economic History, 2022)
This article provides the first quantitative evidence of the indirect benefits of shareholders of the Middelburgse Commercie Compagnie (MCC), a Dutch Atlantic trading company and the biggest slave trader in the eighteenth-century Dutch Republic. MCC shares provided its owners with a preferred status as suppliers and customers of the company. This article focuses on two years, 1725 and 1770, and finds that approximately one third of the MCC shareholders in both years acted as suppliers or customers of the company. The financial incentives of the directors appear to be better aligned with the financial interests of the shareholders in 1770 compared to 1725.